2018
DOI: 10.4081/audiores.2018.198
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Musicians on Ear Protection and Tinnitus: A Preliminary Study

Abstract: Music induced hearing loss (MIHL) is linked to chronic, extended exposure, and progress at a rate proportionate to exposure conditions. The aim was to document hearing deterioration; awareness of ear protection devices (EPDs); presence of tinnitus, measurement of temporary threshold shift. Thirty-four musicians filled a questionnaire regarding: years of experience, instrument/splayed, hours of music exposure per week with/without amplification, through earphones and speakers, use of EPDs and tinnitus. Hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The fact that most participants in this study reported not using hearing protection when exposed to loud music was expected, especially when considering the informal nature of their musical activities. Musicians generally lack awareness about hearing conservation to prevent NIHL (Pouryaghob et al, 2017 ; Dinakaran et al, 2018 ) and therefore do not usually follow proper hearing conservation practices (Santucci, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that most participants in this study reported not using hearing protection when exposed to loud music was expected, especially when considering the informal nature of their musical activities. Musicians generally lack awareness about hearing conservation to prevent NIHL (Pouryaghob et al, 2017 ; Dinakaran et al, 2018 ) and therefore do not usually follow proper hearing conservation practices (Santucci, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pouryaghoub et al ( 2017 ) reported that most musicians do not have adequate knowledge about hearing conservation and therefore, most of them never use protective devices to prevent NIHL. Also, despite musicians being at risk of many auditory disorders because of exposure to loud music, most of them are less concerned about these issues and therefore do not use hearing protection (Dinakaran, Deborah, & Thadathil, 2018 ; Santucci, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has explored the impact of NIHL in musicians [30][31][32][33][34][35][36][37] the genre of music played [19,38,39], and the type of instrument played and the influence of the position of the instrument or musician on the experience of tinnitus [19,35,[40][41][42]. There is still little known however about the lived experience of tinnitus for musicians.…”
Section: Introductionmentioning
confidence: 99%
“…If happen hearing loss to the musicians, it affects their abilities to perform and limits employment opportunities, as well as affecting general quality of life. To avoid tinnitus and promote hearing health among musicians, there is a need for specialized self-help groups, awareness raising, and education (Dinakaran T 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is particularly true for amateur musicians who might not even think they are at risk for NIHL. The majority of musicians lack sufficient understanding about hearing conservation and as a result, they never utilize ear protective to prevent NIHL or do not wear hearing protection (Dinakaran 2018). Furthermore, musicians only use hearing protection on rare occasions, mainly because they find it difficult to perform optimally when wearing hearing protection (Santoni and Fiorini, 2010).…”
Section: Introductionmentioning
confidence: 99%